Proceedings of the Universitas Indonesia International Psychology Symposium for Undergraduate Research (UIPSUR 2017) 2018
DOI: 10.2991/uipsur-17.2018.42
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Strategy on Completion of Mathematics Word Problem and Mathematics Achievement among 3rd Grade Elementary Students

Abstract: One of the fundamental sciences to be learned is mathematics. In Indonesia, students learn mathematics even from preschool up to higher education. Nevertheless, based on the international studies, the Programme for International Student Assessment (PISA) and the Trends in International Mathematics and Science Study (TIMMS) in 2015, mathematics achievement of Indonesian students are still ranked at the bottom. Mathematics achievement is closely related to the cognitive domain, which not only requires cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Overall, it can be said that learning strategies, from each type (cognitive and metacognitive) in all learners regardless of gender are very effective on the degree of their learning in different courses, be it social or natural sciences. Cahayasti and Indrasari (2017) examined the association between the use of metacognitive strategy on the completion of mathematics word problems and mathematics achievement among grade three elementary students. The results indicated that there was a significant positive relationship between the use of metacognitive strategy and mathematics achievement among grade three elementary students (r = 0.35, p < 0.01, 1-tailed).…”
Section: Cognitive and Metacognitive Operationsmentioning
confidence: 99%
“…Overall, it can be said that learning strategies, from each type (cognitive and metacognitive) in all learners regardless of gender are very effective on the degree of their learning in different courses, be it social or natural sciences. Cahayasti and Indrasari (2017) examined the association between the use of metacognitive strategy on the completion of mathematics word problems and mathematics achievement among grade three elementary students. The results indicated that there was a significant positive relationship between the use of metacognitive strategy and mathematics achievement among grade three elementary students (r = 0.35, p < 0.01, 1-tailed).…”
Section: Cognitive and Metacognitive Operationsmentioning
confidence: 99%